Optimal coverage in the futures market under price risk and yield - Guízar Mateos, Isaí; Martínez Damián, Miguel A.; Valdivia-Alcalá, Ramón (Revista Mexicana de Ciencias Agrícolas, 2018)
In Mexico in the last decade has been increasingly greater use of contracts in the futures market to manage risk in agriculture. This paper presents the calculation of optimal coverage for farmers of corn (Zea mays L.) in Jalisco in the futures market using a mean-variance model, this model assumes that the utility function consists of the expected income and variance of income, it is considered that the future price, the spot price and yield represent sources of risk to the producer. The means of these variables are estimated conditional on past information of the same models using autoregressive and moving means. The calculation also uses a range of coefficients of absolute risk aversion. The results suggest that the lower the volatility risk aversion increases the expected income and the higher the risk aversion size remained constant coverage stabilizes at a certain level.
Keywords: risk aversion; coverage; future markets; expected income